Molecular mechanisms of hormones implicated in migraine and the translational implication for transgender patients - Martinez, Cameron I.; Liktor-Busa, Erika; Largent-Milnes, Tally M. (Frontiers in Pain Research, 2023)
Migraine is a primary headache disorder recognized by the World Health Organization as one of the most poorly understood and debilitating neurological conditions impacting global disability. Chronic pain disorders are more frequently diagnosed among cisgender women than men, suggesting that female sex hormones could be responsible for mediating chronic pain, including migraine and/or that androgens can be protective. This review discusses the major gonadal hormones, estrogens, progesterone, and testosterone in the context of molecular mechanisms by which they play a role in migraine pathophysiology. In addition, the literature to date describing roles of minor sex hormones including prolactin, luteinizing hormone, follicular stimulating hormone, and gonadotropin releasing hormone in migraine are presented. Because transgender and gender non-conforming (trans*) individuals are an underserved patient population in which gender-affirming sex hormone replacement therapy (HRT) is often medically necessary to align biological sex with gender identity, results from cisgender patient populations are discussed in the context of these major and minor sex hormones on migraine incidence and management in trans* patients.